IMPROVISATION: AN ESSENTIAL REQUIREMENT FOR EFFECTIVE TEACHING AND LEARNING - Dalhatu, Ibrahim Isah (Sokoto Educational Review, 2012)
Effective teaching and learning can be achieved when proper and adequate teaching materials are utilized, but nowadays, such materials are in short supply in the various institutions of leaving. There is a need for teachers to be conversant with the process of improvisation in order to bridge the gap created. Many educators and other stakeholders believe that they need to improvise become necessary because of the large students' population and scarcity as well as the high cost of imported instructional materials. Several factors are considered while improvising instructional materials. Some of the factors include, Teachers should save materials whenever possible. Also, the materials when constructed must be easily understandable to the learners. In guiding the development of instructional materials the teacher must consider among other things the need for the material, the objectives of the lesson, the learning content and activities etc. Finally, the following recommendations were made (i)Teachers should strive to produce the needed materials (ii) they should be safety conscious during the process.